1994
DOI: 10.1039/c39940002777
|View full text |Cite
|
Sign up to set email alerts
|

Constructing PbI2 nanoparticles into a multilayer structure using the molecular deposition (MD) method

Abstract: MD films are adopted as matrices for the assembly of Pblz nanoparticles into a layer structure; UV-VIS and X-ray diffraction results prove that the multilayers formed have a well-defined layer structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…By using rigid ionic platelets for ESA, such as exfoliated montmorillonite, hectorite, graphite oxide, a-Zr(HPO 4 ) 2 , or niobates, interdiffusion and interface waviness of the adsorbed layers can be suppressed 195) to such an extent that Bragg peaks may be found in X-ray studies 119, 121, 150, 270, 277, 311-313, 315, 322-324, 435) . Similarly, Bragg peaks occasionally show up for ESAfilms made with aggregates of bolaamphiphiles 79,105,107,109) , or with nanoparticles if the spacer layer is thick enough to avoid overlap of the layers containing the particles 270,286,293,434) . Still, such reports are exceptional.…”
Section: The Structure Of Polymer Films Made By Esamentioning
confidence: 95%
See 1 more Smart Citation
“…By using rigid ionic platelets for ESA, such as exfoliated montmorillonite, hectorite, graphite oxide, a-Zr(HPO 4 ) 2 , or niobates, interdiffusion and interface waviness of the adsorbed layers can be suppressed 195) to such an extent that Bragg peaks may be found in X-ray studies 119, 121, 150, 270, 277, 311-313, 315, 322-324, 435) . Similarly, Bragg peaks occasionally show up for ESAfilms made with aggregates of bolaamphiphiles 79,105,107,109) , or with nanoparticles if the spacer layer is thick enough to avoid overlap of the layers containing the particles 270,286,293,434) . Still, such reports are exceptional.…”
Section: The Structure Of Polymer Films Made By Esamentioning
confidence: 95%
“…Stable colloidal dispersions of charged silica 44,73,[264][265][266][267][268][269] , metal oxides 11,36,42,68,72,121,150,244,264,265,[270][271][272][273][274][275][276][277][278][279][280] , polyoxometalates 211,274,278,[281][282][283][284] , semiconductor nanoparticles 90,107,183,186,261,[270][271][272][284][285][286][287][288][289][290]…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…Proposed structure for multilayer alternating PbI2 films prepared using a molecular deposition method. 157 emission varied from red to yellow by changing the size of the nanocrystals. More recently, devices fabricated from single nanocrystals have been proposed such as a single-electron transistor based on CdSe nanocrystals, deposited on a SiO 2 /Si substrate using alkanethiols as circuit wires, Figure 10.…”
Section: -6 2mentioning
confidence: 99%
“…156 Nanostructures can also be prepared by the assembly of preformed nanocrystallites, as in the formation of molecular deposition (MD) films via electrostatic attractions between opposite-charged species. 157 Figure 7 shows a schematic structure obtained by the assembly of anionic PbI 2 nanocrystallites using bipolar pyridinium salt as the cationic species. Self-assembled monolayers have been used to attach CdS nanocrystals to metal substrates via carboxylate or alkanedithiol molecules.…”
Section: Processabilitymentioning
confidence: 99%
“…Indeed, Early work by Shen and co-workers has shown that electrostatic assembled multilayers featuring PbI 2 particles of 3.8 nm exhibit well-defined XRD patterns. [26] The amplitude of F modulation is also determined by the polarisability of the deposited layers. In the case of Au particles of 1.5 AE 0.4 nm, the amplitude of modulation is significantly smaller than for particles of larger diameter.…”
mentioning
confidence: 99%